Determination of auto-recloser location using cost analysis in the sabah electricity distribution network - Hashim A.H.; Mohamad A.M.; Abidin I.Z.; Baharuddin M.Z.; Yeoh E.C. (IEEE Computer Society, 2023)
Sabah Electricity (SESB) operates a vertically integrated electricity utility in East Malaysia. It is currently embarking on an initiative to improve the reliability of its 11kV distribution network which is prone to trippings due to vegetation growth along their long spur lines. Apart from rentice management, another proposed solution is to install auto-reclosers (AR) at appropriate locations in their network. This work deals in developing a methodology to determine the most economic location of ARs and their numbers to be installed. In order to do that, data in the form of customer types, load levels and network topology were collected from site visits at SESB. The study then used an estimated Value of Lost Load (VoLL) to quantify the financial losses that customers suffer given a loss of supply. These losses would then be summed with the cost of ARs for a particular AR placement scenario to form an objective function. The best placement and numbers of AR can be decided by determining the least cost option from the said objective function. 2006 IEEE.